Bridging the gap between overseas and Chinese perceptions on Sino-Middle Eastern relations: a Chinese perspective. Issue 2 (17th February 2021) - Zhang, Chuchu; Xiao, Chaowei
ABSTRACT: Along with China's growing presence and influence in the Middle East, there are many misconceptions about Sino-Middle Eastern relations. This article unravels two questions: How has China understood the role of the Middle East in recent years? How has China framed its own role in the region? To address these questions, the article examines the reports of Sino-Middle Eastern relations in Chinese official media, and articles written by Chinese diplomats and scholars. Based upon content analysis, we find that neither the role of the Middle East nor the role of China itself has fundamentally changed in Chinese narratives. Although China has realized the necessity to adjust its role in the region, such idea is still abstract, immature, and ambiguous. The fact that China often proposes new diplomatic concepts before filling it with concrete substance is a root of the gulf between overseas and Chinese perceptions on Sino-Middle Eastern relations.